2021
DOI: 10.18502/ijm.v13i4.6974
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymphadenopathy and prognosis of COVID-19 disease

Abstract: Background and Objectives: There are conflicting studies on the prevalence of mediastinal lymphadenopathy (LAP) and its relationship to the prognosis of COVID-19 disease. The prevalence varied from 3.4 to 66 percent and more prevalent in pa- tients who died. This study aimed to investigate the mediastinal lymphadenopathy and the disease progression in COVID-19 patients. Materials and Methods: In this case-control study, 195 COVID-19 patients were divided into two groups, with the medias- tinal lymphadeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In total, 21 studies were included in the analysis 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 21 studies were included in the analysis 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Qayyum et al examined 150 patients with acute COVID-19 infection and found prevalent mediastinal lymphadenopathy with a frequency of 23.2 % 34 . Moreover, they did not observe any connection between lymphadenopathy and mortality 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, two studies except Sardanelli F. et al's study reported a relationship between older age and MLNE 12 , 20 , 33 . Angiotensin-converting enzyme 2 (ACE-2) is important in the entry of the virus into the cell, and its expression increases with age, so there is a higher risk for Covid-19 mortality in the elderly 34 .…”
Section: Discussionmentioning
confidence: 96%
“…In a study by Pilechian et al the prevalence of mediastinal lymphadenopathy in COVID-19 disease was 17.4%, while gender and comorbidities such as diabetes, hypertension, and cardiovascular disease were not associated with mediastinal lymphadenopathy. They also found significant differences in oxygen saturation, length of hospital stays, invasive ventilation, ICU admission during hospitalization, disease progression, and COVID-19 severity between people with and without lymphadenopathies [ 5 ]. Sardanelli et al reported that mediastinal lymphadenopathy was more prevalent in individuals who died during the hospital stay and in those with consolidation and crazy paving patterns on radiological findings [ 6 ].…”
mentioning
confidence: 99%
“…The germinal centers and marginal sinus vanished in some lymph nodes, and the remaining lymphatic sinus was filled with monocytes and plasmacytoid monocytes [ 12 ]. Laboratory testing revealed that the COVID patients with the lymphadenopathy had a considerably lower absolute lymphocyte count, higher ESR values, and a higher Neutrophil-to-Lymphocyte Ratio [ 5 ]. Extrapulmonary spread and direct SARS-CoV-2 particle effect on mediastinal lymph node tissues may produce lymphopenia in COVID-19 patients.…”
mentioning
confidence: 99%